2014
DOI: 10.1088/0004-637x/798/1/24
|View full text |Cite
|
Sign up to set email alerts
|

The Survey of Lines in M31 (Slim): Investigating the Origins of [C Ii] Emission

Abstract: The [C ii] 158 µm line is one of the strongest emission lines observed in star-forming galaxies, and has been empirically measured to correlate with the star formation rate (SFR) globally and on ∼ kpc scales. However, due to the multi-phase origins of [C ii], one might expect this relation to break down at small scales. We investigate the origins of [C ii] emission by examining high spatial resolution observations of [C ii] in M 31, with the Survey of Lines in M 31 (SLIM). We present five ∼ 700×700 pc (3 ×3 ) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 93 publications
(142 reference statements)
5
66
0
Order By: Relevance
“…Since the ionization potential of O + is 35.1 eV, [O III] is seen in hot diffuse ionized gas (e.g., Hii regions or the hot ionized medium), where the transition is easily excited (n cr ∼ 5.1 × 10 2 cm −3 and E u /k B ∼ 163 K). Although they trace different ISM phases, all three fine-structure lines have been proposed as tracers of the star formation rate (SFR) of galaxies (Kapala et al 2015;Herrera-Camus et al 2015). For example, De Looze et al (2014) found the line emissions to correlate with the SFRs for a sample of local and high-z starburst galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Since the ionization potential of O + is 35.1 eV, [O III] is seen in hot diffuse ionized gas (e.g., Hii regions or the hot ionized medium), where the transition is easily excited (n cr ∼ 5.1 × 10 2 cm −3 and E u /k B ∼ 163 K). Although they trace different ISM phases, all three fine-structure lines have been proposed as tracers of the star formation rate (SFR) of galaxies (Kapala et al 2015;Herrera-Camus et al 2015). For example, De Looze et al (2014) found the line emissions to correlate with the SFRs for a sample of local and high-z starburst galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Maps of luminous infrared galaxies resolved at 24 μm from GOALS (Armus et al 2009) were convolved to match the 160 μm resolution using the convolution kernel methodology of Aniano et al (2011). To minimize any possible effects of starlight contamination at shorter wavelengths (see, e.g., Kapala et al 2015), the calibration of total infrared (TIR, 3-1100 μm) luminosity was performed utilizing 70, 100, and 160 μm photometry, which closely tracks full-SED integrated TIR luminosity (Galametz et al 2013). …”
Section: Ancillary Datamentioning
confidence: 99%
“…The fields and data are also used by Kapala et al (2015) to trace the origin of [CII] line emission, as part of the Survey of Lines in M31 (SLIM, PI Sandstrom K.). The positions of the five fields are shown in Fig.…”
Section: Datamentioning
confidence: 99%